Extensive Sclerosing Mesenteritis of the Rectosigmoid Colon Associated with Erosive Colitis - C. Nobili; L. Degrate; R. Caprotti; C. Franciosi; B. E. Leone; F. Romano; M. Dinelli; Fr. Uggeri (Gastroenterology Research and Practice)
Sclerosing mesenteritis is a rare, idiopatic, usually benign, inflammatory process of the mesenteric adipose tissue. The most common site of involvement is the small bowel mesentery. We present a case of sclerosing mesenteritis of the rectosigmoid colon as a cause of severe abdominal pain, abdominal obstruction, and ischemic colic mucosal lesions. Contrast enema, colonoscopy, angiography, and CT were the imaging modalities used. A 20 cm diameter, fibrotic mass causing extensive compression of rectosigmoid colon was found at laparotomy. Histological examination showed extended fibrosis, inflammatory cells infiltration, lipophages, and granulomas within the mesenteric adipose tissue associated with erosive colitis. Clinical presentation and treatment are discussed.